New Developments in Chiral Phosphoric Acid Catalysis for Amine Synthesis - Neupane, Bishnu P.; Friestad, Gregory K. (Current Organic Chemistry, 2022)
Asymmetric catalysis with chiral phosphoric acids (CPAs) has impacted a wide range of organic reactions, including those that generate chiral amines of interest in medicinal and natural products chemistry. Phosphodiester derivatives (RO)2PO2H offer linkages to various chiral alcohols and diols, permitting the CPA to transmit stereochemical information to reactants via ion-pairing and/or H-bonding interactions of the P=O and O–H bonds. This minireview presents selected recent developments in CPA-catalyzed asymmetric synthesis of amines, emphasizing innovations from the literature of 2017–2021, with a few earlier examples to provide additional context. The coverage includes additions to imines, asymmetric protonation, induction of axial asymmetry, asymmetric Ugi and Passerini multicomponent coupling reactions, hydroaminations, and Minisci-type additions to heteroaromatic systems.
Keywords: enantioselectivity